1993
DOI: 10.1002/ajhb.1310050307
|View full text |Cite
|
Sign up to set email alerts
|

Weights of brain, heart, liver, kidneys, and spleen in healthy and apparently healthy adult Danish subjects

Abstract: Based on a forensic material of 1,598 autopsies of Danish adults (1,086 males, 512 females ≥ 16 years of age), who prior to death were healthy or apparently healthy based on clinical evidence, the weights of brain, heart, liver, kidneys, and spleen were registered. The variability of organ weights was estimated. Relationships between organ weights and body size, and among organ weights were also evaluated. Males had larger organ weights than females. When organ weights were based on the same estimated fat free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
1
6

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 4 publications
4
48
1
6
Order By: Relevance
“…However, there might also be a possibility that we overestimated calculated RMR of the elderly. Although the sum of organ masses as calculated with the equations from Garby et al (1993) in our study was significantly lower in the elderly when compared to young subjects, heart mass was nevertheless significantly higher in the elderly. As discussed by Bosy-Westphal et al (2003), an increased heart mass could also add to the observed age-group differences between measured and calculated RMR in case the heart metabolic rate decreased with an increasing heart mass in the elderly.…”
Section: Discussioncontrasting
confidence: 66%
See 4 more Smart Citations
“…However, there might also be a possibility that we overestimated calculated RMR of the elderly. Although the sum of organ masses as calculated with the equations from Garby et al (1993) in our study was significantly lower in the elderly when compared to young subjects, heart mass was nevertheless significantly higher in the elderly. As discussed by Bosy-Westphal et al (2003), an increased heart mass could also add to the observed age-group differences between measured and calculated RMR in case the heart metabolic rate decreased with an increasing heart mass in the elderly.…”
Section: Discussioncontrasting
confidence: 66%
“…The magnitudes of the differences were 612 and 601 kJ/day, respectively, for women and men and are very similar to those observed in our study (625 and 515 kJ/day). This correspondence of the results is even more remarkable in that by contrast to the study of Gallagher et al (2000) organ masses were not measured in our study but derived from the regression equations developed by Garby et al (1993). Bosy-Westphal et al (2003) also measured RMR and body composition including several organ masses in 26 young (13 females, 13 males) and 26 elderly subjects (15 females, 11 males) and specific organ metabolic rates were taken from the literature.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations